PENTINGNYA PENERAPAN MANAJEMEN DAN KEPEMIMPINAN ROHANI MUSA DI KELUARAN 18:1-27 DALAM KEPEMIMPINAN GEREJA MASA KINI - Costa, Efraim Da; Permatasari, Ayu Dewi (Sekolah Tinggi Teologi Hagiasmos Mission, 2022)
Moses was one of the greatest leaders of the Old Testament. Through Moses' leadership of the Israelites, the church today can learn valuable lessons that are still relevant to be applied in church management and leadership. Moses was the revolutionary leader because he implemented new things that made his ministry much more efficient and effective. He does not insist to maintain his previous leadership style which focuses on “one man show” leadership, but he is known as an administrative leader who creates a leadership system that is even widely applied in secular management applications. In this journal, we will discuss five keys to the success of Moses' leadership in Exodus 18:1-27: (1) God’s Love is as a foundation in the Leadership; (2) Humility; (3) Delegation of the Workload; (4) Teaching and Training; (5) Select and Train the Right People. Keywords: Management; Leadership; Spiritual Leadership Abstrak Musa adalah salah seorang pemimpin terbesar dalam Perjanjian Lama. Melalui kepemimpinan Musa terhadap bangsa Israel gereja masa kini dapat memetik pelajaran berharga yang masih relevan untuk diterapkan dalam manajemen dan kepemimpinan gerejawi. Musa adalah pemimpin yang revolusioner karena ia menerapkan hal baru yang membuat pelayanannya jauh lebih efisien dan efektif. Ia tidak terus menerus mempertahankan cara kepemimpinannya yang lama yang berfokus pada kepemimpinan “one man show”, namun ia dikenal sebagai pemimpin administratif yang membuat sistem kepemimpinan yang bahkan banyak diterapkan di penerapan manajemen sekuler sekalipun. Dalam jurnal ini akan membahas lima kunci keberhasilan kepemimpinan Musa di Keluaran 18:1-27: (1) Kasih Allah sebagai dasar kepemimpinan; (2) Kerendahan Hati; (3) Pendelegasian Beban Pekerjaan; (4) Pengajaran dan Pelatihan; (5) Memilih dan Melatih orang yang tepat. Kata Kunci: Manajemen; Kepemimpinan; Kepemimpinan Rohani